Chronic Methamphetamine Effects on Brain Structure and Function in Rats. - Panayotis K Thanos; Ronald Kim; Foteini Delis; Mala Ananth; George Chachati; Mark J Rocco; Ihssan Masad; Jose A Muniz; Samuel C Grant; Mark S Gold; Jean Lud Cadet; Nora D Volkow (PLoS ONE, 2016)
Methamphetamine (MA) addiction is a growing epidemic worldwide. Chronic MA use has been shown to lead to neurotoxicity in rodents and humans. Magnetic resonance imaging (MRI) studies in MA users have shown enlarged striatal volumes and positron emission tomography (PET) studies have shown decreased brain glucose metabolism (BGluM) in the striatum of detoxified MA users. The present study examines structural changes of the brain, observes microglial activation, and assesses changes in brain function, in response to chronic MA treatment. Rats were randomly split into three distinct treatment groups and treated daily for four months, via i.p. injection, with saline (controls), or low dose (LD) MA (4 mg/kg), or high dose (HD) MA (8 mg/kg). Sixteen weeks into the treatment period, rats were injected with a glucose analog, [18F] fluorodeoxyglucose (FDG), and their brains were scanned with micro-PET to assess regional BGluM. At the end of MA treatment, magnetic resonance imaging at 21T was performed on perfused rats to determine regional brain volume and in vitro [3H]PK 11195 autoradiography was performed on fresh-frozen brain tissue to measure microglia activation. When compared with controls, chronic HD MA-treated rats had enlarged striatal volumes and increases in [3H]PK 11195 binding in striatum, the nucleus accumbens, frontal cortical areas, the rhinal cortices, and the cerebellar nuclei. FDG microPET imaging showed that LD MA-treated rats had higher BGluM in insular and somatosensory cortices, face sensory nucleus of the thalamus, and brainstem reticular formation, while HD MA-treated rats had higher BGluM in primary and higher order somatosensory and the retrosplenial cortices, compared with controls. HD and LD MA-treated rats had lower BGluM in the tail of the striatum, rhinal cortex, and subiculum and HD MA also had lower BGluM in hippocampus than controls. These results corroborate clinical findings and help further examine the mechanisms behind MA-induced neurotoxicity.